2011
DOI: 10.1007/s10812-011-9419-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states of CsLi and CsLi+ molecules

Abstract: The results of the present many-electron configuration interaction calculations on the cation support the previous core-polarization effective potential calculations. The present calculations on the CsLi molecule are complementary to previous theoretical work on this system, including recently observed electronic states that had not been calculated previously. We have used an ab initio approach involving a nonempirical pseudopotential for the Li (1s 2 ) and Cs cores and a core-valence correlation correction. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…A rather good agreement is observed for the equilibrium distance, however their potential is much deeper. Reasonably good agreement between our spectroscopic constant and those of Khelifi et al [58] is observed for the 2 2 Σ + and 3 2 Σ + states. The difference between Khelifi et al spectroscopic constants and our results are found to be 2.58% and 10.35% for R e and D e , respectively.…”
Section: Spectroscopic Constantssupporting
confidence: 90%
See 2 more Smart Citations
“…A rather good agreement is observed for the equilibrium distance, however their potential is much deeper. Reasonably good agreement between our spectroscopic constant and those of Khelifi et al [58] is observed for the 2 2 Σ + and 3 2 Σ + states. The difference between Khelifi et al spectroscopic constants and our results are found to be 2.58% and 10.35% for R e and D e , respectively.…”
Section: Spectroscopic Constantssupporting
confidence: 90%
“…The spectroscopic constants of (LiCs) + and (NaCs) + , are presented respectively in tables 2 and 3 and compared with the available theoretical results [58,50]. To the best of our knowledge there is no experimental data for these ionic molecules.…”
Section: Spectroscopic Constantsmentioning
confidence: 98%
See 1 more Smart Citation
“…The spectroscopic constants of (LiCs) + and (NaCs) + , are presented respectively in tables 4-4 and compared with the available theoretical results [50,58]. To the best of our knowledge there is no experimental data for these ionic molecules.…”
Section: Pseudopotential Method: Results and Discussionmentioning
confidence: 99%
“…To the best of our knowledge there is no experimental data for these ionic molecules. For the (LiCs) + ionic molecule, we compare our results only with the theoretical work of Khelifi et al [58] where they used a similar method as used in our work. They reported for the ground state S + 1 2 the spectroscopic constants R e = 7.91 a.u.…”
Section: Pseudopotential Method: Results and Discussionmentioning
confidence: 99%